Massive neurocysticercosis in a ten-year-old girl: a case report - Guoguang Xiao; Min Shu (BMC, 2024)
Abstract Background Massive neurocysticercosis is a rare form of neurocysticercosis, and can lead to serious conditions and even death. Case presentation Here we present a case of ten-year-old Tibetan girl who developed headache and vomiting. Her brain magnetic resonance imaging (MRI) illustrated lots of intracranial cystic lesions, and no obvious extracranial lesions were found. Serum immunoglobulin G antibodies against cysticerci were positive by the use of an enzyme-linked immunosorbent assay (ELISA). These results in combination with her medical history were in line with massive neurocysticercosis. The patients recovered well after supportive management and antiparasitic treatment. Conclusions This case provides insights on the diagnosis and treatment of massive neurocysticercosis. The treatment of patients with massive neurocysticercosis should be in an individualized fashion, and the use of antiparasitic drugs in these patients must be decided after carefully weighing the risks and benefits.